If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13=g/3+4g
We move all terms to the left:
13-(g/3+4g)=0
Domain of the equation: 3+4g)!=0We add all the numbers together, and all the variables
We move all terms containing g to the left, all other terms to the right
4g)!=-3
g!=-3/1
g!=-3
g∈R
-(+4g+g/3)+13=0
We get rid of parentheses
-4g-g/3+13=0
We multiply all the terms by the denominator
-4g*3-g+13*3=0
We add all the numbers together, and all the variables
-1g-4g*3+39=0
Wy multiply elements
-1g-12g+39=0
We add all the numbers together, and all the variables
-13g+39=0
We move all terms containing g to the left, all other terms to the right
-13g=-39
g=-39/-13
g=+3
| M-10=-m | | 2(n-12)+1=-2+25 | | -14-0.26=5.4d+14.74-18.2d | | -20+12x=11x+6 | | 5+13(x+11)=8x+6/7 | | 0.75x+6=0.5x+3 | | n+1=−15 | | 3.7x-41.3=5.4x+29.4 | | -6(u+3)=36 | | 1-b-6=-6 | | 12j-18=18+3j | | -2(n-12)+1=-2+21 | | 5(5x+3x+7)=0 | | 180=(8x+6)+62 | | v+9/3=8=v | | x(56)=168 | | .4x-1=15 | | -4a-a=15 | | -4p-1=11-6p | | 11g=-3+10g | | -6(u+3=36 | | 1-2n+6n=5 | | |2x-9|=27-x | | 4q+20=-15q-18 | | 5(-2x-2)−2x−4=10 | | 3x-6x+10=2x+20 | | 2/3x2/3=16 | | 7x+7=2x+2=90 | | 3-6w+6=-9 | | 18-5v=-14-v+12 | | 7x=13-6x | | 3p-6+5=-13 |